Legal education on juvenile delinquency - Kurniaty, Yulia; Nurwati, Nurwati; Basri, Basri; Krisnan, Johny (Universitas Muhammadiyah Magelang, 2021)
35% of the population of Seneng, Banyurojo Village, Mertoyudan District, Magelang Regency are of school age. They begin to actively interact with peers, both from their home and school environment, both direct interaction and through social media. Interaction during the socialization process is feared to have a negative impact on children's behavior towards criminal acts. For this reason, prevention efforts need to be made so that cases of children in conflict with the law do not occur through legal counseling activities. The result of legal education counseling activities regarding juvenile delinquency is to increase the understanding of PKK Dusun Seneng women about the various juvenile delinquency, the causal factors and efforts to prevent children from being involved in crime. Strengthening legal understanding for PKK members of Dusun Seneng was useful in the parenting process, so that they are able to support the vision of Banyurojo Village point 7. It is to encourage the realization of a village community that is religious, dignified and cultured and has noble character to create a harmonious, orderly, safe and peaceful social life.